FUNDAMENTALS OF PATHOLOGOANATOMIC DIAGNOSTICS IN POISONING - O.A. Djurayev (Western European Studies, 2024)
The article covers the general principles of the clinical course, the dynamics of the processes of anatomical manifestation in internal organs and tissues, pathological diagnosis of poisoning, information on the analysis and generalization of the results of autopsy of corpses, as well as the causes of poisoning of farm animals. Autopsy data are presented for the most common poisonings of animals with substances such as certain chemical elements and their compounds, gaseous substances and plant poisons. Information is provided on intravital pathological processes, mechanisms of death and the severity of cadaveric phenomena when assessing the results of the autopsy.
Keywords: poisonings; clinic; dynamics; toxicosis